2014
DOI: 10.4067/s0718-19572014000300020
|View full text |Cite
|
Sign up to set email alerts
|

Efecto del endoparásito Prosorhynchoides sp. (Trematoda: Bucephalidae) en la capacidad de nado sostenido del baunco Girella laevifrons (Osteichthyes: Kyphosidae)

Abstract: Efecto del endoparásitoAbstract.-This study analyzed whether the trematode Prosorhynchoides sp., at metacercaria stage, affects the sustained swimming capacity of the intertidal juvenile sea chub Girella laevifrons. Fifteen non-parasitized and 15 experimentally infested fish were used in this study. Wild fish were infested under laboratory conditions by cercar ia from an infected mussel Perumytilus purpuratus. The parasite mainly infested the tail muscles of the fish. The maximum time of sustained swimming of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Some parasites affect the swimming performance of their second intermediate hosts. This occurs in kyphosid fish Girella laevifrons infected with metacercariae of the bucephalid Prosorhynchoides sp., which encyst mainly in the tail fin [ 69 ]. However, the reduction in swimming performance of the fish is not proportional to the intensity of infection, suggesting that, rather than physical interference, the metacercariae may have other effects, such as causing inflammation, localized hemorrhage, or cell destruction, all of which are metabolically demanding [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some parasites affect the swimming performance of their second intermediate hosts. This occurs in kyphosid fish Girella laevifrons infected with metacercariae of the bucephalid Prosorhynchoides sp., which encyst mainly in the tail fin [ 69 ]. However, the reduction in swimming performance of the fish is not proportional to the intensity of infection, suggesting that, rather than physical interference, the metacercariae may have other effects, such as causing inflammation, localized hemorrhage, or cell destruction, all of which are metabolically demanding [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…This occurs in kyphosid fish Girella laevifrons infected with metacercariae of the bucephalid Prosorhynchoides sp., which encyst mainly in the tail fin [ 69 ]. However, the reduction in swimming performance of the fish is not proportional to the intensity of infection, suggesting that, rather than physical interference, the metacercariae may have other effects, such as causing inflammation, localized hemorrhage, or cell destruction, all of which are metabolically demanding [ 69 ]. In the grass shrimp Palaemonetes pugio , metacercariae of the microphallid Microphallus turgidus encyst mainly in the abdominal muscles, and although swimming of the shrimp can be severely affected, this effect is also independent of the intensity of infection [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Parasitic copepods may be too heavy for fish larvae which may affect the ability of the fish to swim. There is evidence that a few metacercariae in juvenile Girella laevifrons significantly affect the swimming time of the fish (Rebolledo et al 2014). We have also recently observed that the average volume of prey eaten by parasitized fish larvae was smaller than in fish without parasites because parasitized fish eat smaller prey and these prey were less mobile (gastropod larvae) than the most frequently ingested prey of unparasitized fish larvae (i.e., copepodites and nauplii) (Janhsen-Guzman et al, unpublished).…”
Section: Discussionmentioning
confidence: 99%